Synthesis and polymorphism of a new phase 1D chalcogenide M2N3X8 structure based on the periodic table: Ta2Ni3S8 with a tetragonal structure - Jeon, Jiho; Woo, Chaeheon; Choi, Kyung Hwan; Jeong, Byung Joo; Kang, Jinsu; Zhang, Xiaojie; Dong, Xue; Kim, Tae Yeong; Ahn, Jungyoon; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (Journal of Alloys and Compounds, 2022)
For the first time, a new structure of Ta2Ni3S8, one of the family systems of M2N3X8, a recently studied one-dimensional chalcogenide material, was synthesized. Unlike Ta2Ni3S8 in the orthorhombic phase, which is known to have semiconductor properties, Ta2Ni3S8 in the tetragonal phase displayed metallic material properties. Structural analysis through X-ray diffraction confirmed that the tetragonal Ta2Ni3S8 (T-Ta2Ni3S8) had the same structure as the tetragonal Ta2Ni3Se8 (T-Ta2Ni3Se8), a material with an S- and Se- substitution; the only difference was the lattice constant. Additionally, different elemental analyses were used to confirm that the ratio of Ta:Ni:S elements was 2:3:8. This study is significant as basic research that can be applied to various electronic devices by applying bandgap tuning and lattice-matched electrode design based on M2N3X8 family material.
Keywords: 1d chalcogenide M2N3X8; Chalcogenide materials; Low-dimensional materials; One-dimensional; Orthorhombic phase; Periodic table; Semiconductors properties; Structure-based; Synthesised; Tetragonal structure; 1D chalcogenide M2N3X8; Low-dimensional materials; Polymorphism; Ta2Ni3S8